Group level scientometric analysis of Pakistani authors. Issue 2 (3rd July 2021) - Wahid, Nazia; Warraich, Nosheen Fatima; Tahira, Muzammil
Abstract : The study aims to analyze the most productive Pakistani authors by using scientometric approach based on the Web of Science (WoS) data to perform group level comparative analysis. One hundred most productive authors have been recognized from ten years data of top ten universities ranked in WoS. Their publication data has been extracted for further analysis. We applied traditional metrics, h-index, h-type and composite indices. The authors have been divided into four groups, named Top Authors (N=31), Big Producers (N=18), Selective Authors (N=19) and Low Productive Authors (N=32). Descriptive and inferential statistics were performed. Findings revealed that h-index, h-type and composite indices clearly differentiate upper and lower groups. However, the discrimination between middle groups is indistinct. The functional relationship of total citations of all groups with the h-type and composite indices is found better as compared to the other traditional metrics. Total citations of top authors, selective authors and low productive authors has strong relationship with g-index and p-index except big producers. Moreover, total citations has strong relationship with h-index at top author level, moderate relation with big producers and low productive authors and poor at selective author level. The relationship of citations per publications of all groups with the h-type and composite indices was found moderate or poor except p-index. It was observed that publications counts of all groups has weak relationship with all indices. The study adds insight into the discrimination of groups of Pakistani authors using different scientometric indices. It may be of interest to those concerned in research performance evaluation metrics.